In utero spontaneous bladder rupture in a fetus with posterior urethral valve: A case report of prenatal diagnosis and management. Issue 7 (19th April 2018) - Magawa, Shoichi; Tanaka, Hiroaki; Nii, Masafumi; Maki, Shintaro; Kamimoto, Yuki; Ikeda, Tomoaki
Abstract: Posterior urethral valve (PUV) rarely causes bladder rupture. We experienced hydronephrosis due to ureteral obstruction after the natural repair of a ruptured bladder in a fetus with PUV. Fetal ascites and oligohydramnios were diagnosed at 26 weeks' gestational age. While we followed up with ultrasonography, we regularly removed the fetal ascites via abdominal puncture, injecting warm saline instead of amniotic fluid. At 35 weeks' gestational age, the infant was diagnosed with severe bilateral hydronephrosis, absent of ascites and oligohydramnios. Therefore, a Caesarean section was performed. After birth, the infant was diagnosed with hydronephrosis due to ureteral obstruction after the natural repair of a ruptured bladder associated with PUV. Thus, a ruptured bladder in a fetus with PUV that has naturally repaired should be closely monitored via ultrasonography for hydronephrosis due to ureteral obstruction.